2013
DOI: 10.1186/1471-2431-13-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of an early intervention program for preschool children with Autism Spectrum Disorder in a community group setting

Abstract: BackgroundAvailable evidence indicates that early intervention programs, such as the Early Start Denver Model (ESDM), can positively affect key outcomes for children with Autism Spectrum Disorder (ASD). However, programs involving resource intensive one-to-one clinical intervention are not readily available or deliverable in the community, resulting in many children with ASD missing out on evidence-based intervention during their early and most critical preschool years. This study evaluated the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 28 publications
7
121
2
4
Order By: Relevance
“…Given the critical relevance of early cognitive and language skills for long-term outcomes in ASD (Howlin et al 2009, the ESDM program appears to be a promising approach for pre-schoolers with ASD not only in the context of 1:1 delivery (as documented by Dawson et al 2010) but also in community-based group settings. Results of our controlled study are also consistent with those reported in Eapen et al (2013) and Vivanti et al (2013), providing further support for the usefulness of this approach in the context of group-based community settings. Further research is needed to replicate and extend the results presented here and to analyse the cost-effectiveness of this program in the short and long term.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Given the critical relevance of early cognitive and language skills for long-term outcomes in ASD (Howlin et al 2009, the ESDM program appears to be a promising approach for pre-schoolers with ASD not only in the context of 1:1 delivery (as documented by Dawson et al 2010) but also in community-based group settings. Results of our controlled study are also consistent with those reported in Eapen et al (2013) and Vivanti et al (2013), providing further support for the usefulness of this approach in the context of group-based community settings. Further research is needed to replicate and extend the results presented here and to analyse the cost-effectiveness of this program in the short and long term.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, two recent studies offer preliminary evidence of favourable outcomes following delivery of the ESDM in a group-setting (Eapen et al 2013;Vivanti et al 2013). To date, however, no controlled study has investigated the effectiveness of the ESDM in the context of community-based provision.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The advance of portable technology and the change in social philosophy and legislation to promote caring for children with disability in the home over institutionalization have been instrumental in doubling the number of children with disability being cared for in the home over the past 50 years. 3,4 These achievements are celebrated but accompanied by increased caregiving burden by all members of a household with a child with disability.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have suggested that there are likely many 'autisms' with different underlying biological processes and developmental pathways [3]. In this regard, considerable genetic and clinical heterogeneity has been suggested with significant variations both in the etiological underpinnings and in the manifestations of the condition [4,5]. However, consistent with Kanner's original description, the core features include social and communication deficits as well as an 'insistence on sameness' [6].…”
Section: Introductionmentioning
confidence: 93%
“…In a previous publication, clinical outcomes of ESDM intervention in a subsample of 26 children were presented [4]. The current study involved a larger sample and focused on predictors of treatment response.…”
Section: Participantsmentioning
confidence: 99%